System Approach from Biomass Combustion in Packed Bed Reactor - Ankhien Le; Le Xuan Hai; V. N. Sharifi; J Swithenbank (ASEAN Journal of Chemical Engineering, 2007)
A simple algorithm originally proposed by Choong, Paterson and Scott (2002) was tested on a model of an isothermal controlled-cycled stirred tank reactor with substrate inhibition kinetics, (r = 1 ~c). In previous work, this reacting system had been shown to exhibit steady-state multiplicity. The transition period of this system to the stable steady state is sometimes characterized by very slow change followed by a very rapid convergence to the stable steady state. Tests of the Choong-Paterson-Scott algorithm showed that the feature, which prevents premature termination of the calculations prior to reaching the true steady state, is very useful for this system. However, tests of the stopping criterion showed that the other feature of reducing the computing time was not realized in this system.